Global saturated velocity-free finite-time control for attitude tracking of spacecraft - Xia, Yuquan; Su, Yuxin (IET control theory & applications, 2019)
This study investigates the problem of global finite-time attitude tracking for spacecraft subject to actuator constraints and attitude measurements only. A velocity-free saturated hybrid proportional–derivative (PD) plus spacecraft dynamics (PD+) control is proposed. Benefiting from the hybrid control technique, the unwinding phenomenon is completely avoided and the global stability is achieved. Lyapunov stability theory and homogeneous method are employed to show global finite-time tracking. Advantages of the proposed control include simple and intuitive structure and the absence of velocity measurements, and thus it is ready to implement. An additive feature is that the proposed control is explicitly upper bounded and hence it can assure that actuator constraints will not be violated by selecting the control gains a priori. Simulations are performed to illustrate the effectiveness and improved performance of the proposed approach.